Pneumocystis jirovecii pneumonia in rheumatologic disease: A case report indicating possible need of prophylaxis - Tejas Bende; Yogya Jha; Sushrut Ganpule; Geethu Joe; Rajeev Soman (Archives of Preventive Medicine - Peertechz Publications, 2023)
An 81-year-old female with Granulomatosis and polyangiitis on immunosuppression with methotrexate, steroids, and Rituximab but not on prophylaxis, developed findings of Pneumocystis jirovecii pneumonia (PJP). She was treated with an alternative regimen, clindamycin and primaquine along with caspofungin and corticosteroids. Secondary prophylaxis with cotrimoxazole was initiated after completion of treatment. This case highlights the importance of early diagnosis, treatment difficulties, and the need for prophylaxis for HIV-negative patients on immunosuppressive treatment.